PENGARUH DUKUNGAN SOSIAL TEMAN SEBAYA TERHADAP KEPERCAYAAN DIRI SISWA DI SMA NEGERI 2 KOTA JAMBI - Hutagaol, Haliza Khairiyah; Sutja, Akmal; Lubis, Muhammad Alridho (PABKI (Perkumpulan Ahli Bimbingan dan Konseling Islam) Indonesia, 2024)
The aim of this research is to see whether there is an influence of peer social support behavior on students' self-confidence at SMA Negeri 2 Jambi City. This type of research is quantitative research using the expost-facto method. The population in this study were students from classes XII IPA 1 to The instrument used in this research is a questionnaire and the measurement scale used in this research is the Likert scale. Furthermore, in the statistical assumption test, there are two conditions that must be met, namely the data normality test and the data linearity test, and this research uses a simple regression analysis technique to measure the influence of peer social support behavior (X) on self-confidence (Y) with the help of the SPSS version. 25. The results of this research show that the determination is at 0.175 or 17.5%. The criteria for interpreting the influence of determination of 0.175 or 17.5% are in the quite strong category (0.17 – 0.49), so this research shows that there is a significant influence between the social support variable of peers (X) on self-confidence (Y).